2020
DOI: 10.1186/s40008-020-00220-6
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic linkages between poverty, inequality, crime, and social expenditures in a panel of 16 countries: two-step GMM estimates

Abstract: The study evaluated different United Nation sustainable development goals (SDGs), i.e., goals 1 and 2 (poverty reduction and hunger), goals 3 and 4 (promotion of health and education), goal 10 (reduced inequalities), and goal 16 (reduction of violence, peace and justice) to access pro-poor growth and crime reduction in a panel of 16 heterogeneous countries. The discussion of crime rate in pro-poor growth (PPG) agenda remains absent in the economic development literature, though Bourguignon (2000) stressed to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
51
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(61 citation statements)
references
References 62 publications
4
51
0
6
Order By: Relevance
“…ICTs and innovation in agriculture (e-agriculture) help to ensure food security in three broad categories; through production, postharvest storage, and the supply value chain [1]. It should be noted that while production is an essential factor in ensuring food security, other factors such as access to food and utilisation are also important Anser et al [32].…”
Section: Ict Adoption Innovation and Food Securitymentioning
confidence: 99%
“…ICTs and innovation in agriculture (e-agriculture) help to ensure food security in three broad categories; through production, postharvest storage, and the supply value chain [1]. It should be noted that while production is an essential factor in ensuring food security, other factors such as access to food and utilisation are also important Anser et al [32].…”
Section: Ict Adoption Innovation and Food Securitymentioning
confidence: 99%
“…The Economist magazine recently compiled a list of the world's 50 most violent metropolises (cities with populations of 250,000 or more), and 32 of them are located in the country. 1 Brazil also shares many features with other countries in Latin America and the Caribbean. According to the UNODC, among the 20 most violent countries in the world, 14 are located in the region.…”
mentioning
confidence: 99%
“…The model depicts the effect of certain variables on aggregate crime i.e unemployment (Carr-Hill and Stern, 1983), social sector spending (Anser et al, 2020), education (Khan et al, 2015), population density (Fisher, 1987), per capita income (Syed and Ahmed, 2013), GDP growth (Goulas and Zervoyianni, 2013), poverty (Anser et al, 2020), income inequality (Umair, 2019b;Wu and Wu, 2012) and police strength (Chalfin and McCrary, 2017…”
Section: Aggregated Crime Modelmentioning
confidence: 99%
“…Another study (Anser et al, 2020) investigated the dynamic relationship between socio-economic factors and crime rate in a panel of 16 countries, using a time series data from 1990-2014 and found that income inequality and unemployment rate increase crime rate while trade openness supported to decrease crime rate. Umair (2019) attempted to find socioeconomic determinants of crime in Pakistan which used one dependent variable (crimes) and four independent variables (Population growth, net income, inflation and economic growth).…”
mentioning
confidence: 99%